2022
DOI: 10.21203/rs.3.rs-1993450/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intraoperative Low-dose S-ketamine Reduces Depressive Symptoms in Patients with Crohn’s Disease Undergoing Bowel Resection: A Randomized Controlled Trial

Abstract: Purpose We aim to investigate the effect of S-ketamine preconditioning on postoperative depression in patients with CD undergoing bowel resection with mild to moderate depression and to observe whether it can relieve postoperative pain and anti-inflammation. Methods A total of 120 adult patients were randomised in to one of the two groups; Patients in the S-ketamine group received 0.25mg/kg S-ketamine intravenous drip under general anesthesia induction, followed by continuous infusion of S-ketamine with 0.12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…For example, Tirkolaee et al [21], using optimization methods, to measure the efficiency of some decision-making units, found that the capacity and scale were among the cases for measuring the efficiency of such units and their perspectives. The application of optimization to evaluate system conditions has been further observed in other studies, too [22][23][24].…”
Section: Literature Reviewmentioning
confidence: 76%
See 2 more Smart Citations
“…For example, Tirkolaee et al [21], using optimization methods, to measure the efficiency of some decision-making units, found that the capacity and scale were among the cases for measuring the efficiency of such units and their perspectives. The application of optimization to evaluate system conditions has been further observed in other studies, too [22][23][24].…”
Section: Literature Reviewmentioning
confidence: 76%
“…Considering the fact that the suggested model is on the basis of the queuing concepts, the hotel and its reception and accommodation system should be adapted to the queuing system components [13,22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation